Clinical characteristics, outcomes, and seasonality of acute respiratory infection associated with single and codetected rhinovirus species among hospitalized children in Amman, Jordan. Issue 12 (9th August 2022) - Talj, Rana; Amarin, Justin Z.; Rankin, Danielle A.; Bloos, Sean M.; Shawareb, Yanal; Rahman, Herdi; Haddadin, Zaid; Howard, Leigh M.; Probst, Varvara; Naffa, Randa G.; Johnson, Monika; Lane, Sidney; et al.
Abstract: Rhinovirus (RV)‐specific surveillance studies in the Middle East are limited. Therefore, we aimed to study the clinical characteristics, outcomes, and seasonality of RV‐associated acute respiratory infection among hospitalized young children in Jordan. We conducted a prospective viral surveillance study and enrolled children <2 years old admitted to a large public hospital in Amman, Jordan (2010–2013). Demographic and clinical data were collected by structured interviews and chart abstractions. Nasal and/or throat swabs were collected and tested for a panel of respiratory viruses, and RV genotyping and speciation was performed. At least one virus was detected in 2641/3168 children (83.4%). RV was the second most common virus detected ( n = 1238; 46.9%) and was codetected with another respiratory virus in 730 cases (59.0%). Children with RV codetection were more likely than those with RV‐only detection to have respiratory distress but had similar outcomes. RV‐A accounted for about half of RV‐positive cases (54.7%), while children with RV‐C had a higher frequency of wheezing and reactive airway disease. RV was detected year‐round and peaked during winter. In conclusion, though children with RV codetection had worse clinical findings, neither codetection nor species affected most clinical outcomes.